Digital block with or without the addition of epinephrine in the anesthetic solution - Reis Júnior,Almiro dos (2016)
BACKGROUND AND OBJECTIVES: Review of various techniques for digital blocks with local anesthetic, with or without epinephrine. CONTENTS: Description of various procedures and comparison of results reported in the literature, mainly on latency and quality of anesthesia, details on vasoconstrictor effect of epinephrine, intraoperative bleeding, necessity of tourniquet use, duration of anesthesia and postoperative analgesia, blood flow and digital SpO2 behavior, local and systemic complications, and also approaches and drugs to be used in certain situations of ischemia. CONCLUSIONS: The advantages of adding epinephrine to the anesthetic solution are minor when compared to the risks of the procedure, and it seems dangerous to use a vasoconstrictor in the fingers, unless the safety of the technique and the possibility of discarding the tourniquet are definitely proven.